Alternative biomarkers for classification of latent tuberculosis infection status in pregnant women with borderline Quantiferon plus results. (September 2020) - Tesfaye, Fregenet; Sturegård, Erik; Walles, John; Winqvist, Niclas; Balcha, Taye Tolera; Karlson, Sara; Mulleta, Daba; Isberg, Per-Erik; Jansson, Marianne; Björkman, Per
Abstract: Borderline interferon-gamma (IFN-γ) results (near the cut-off level 0.35 IU/ml) occur in QuantiFERON (QFT) assays. We investigated the performance of alternative biomarkers for classification of latent tuberculosis infection (LTBI) status in pregnant women with borderline QFT IFN-γ responses. Pregnant women (n = 96) were identified from a cohort study in Ethiopia, based on QFT-Plus IFN-γ results (QFT-low: <0.20 IU/ml, n = 33; QFT-borderline: 0.20–0.70 IU/ml, n = 31; QFT-high: >0.70 IU/ml, n = 32), including 12 HIV-positive individuals in each group and with 20 HIV-negative non-pregnant women from the same cohort with QFT IFN-γ <0.20 IU/ml as controls. Concentrations of 8 markers (IL-1ra, IL-6, IL-8, IP-10, MCP-1, MCP-2, osteopontin and resistin) were measured in whole blood QFT supernatants, stimulated separately with TB1 and TB2 antigens. K-nearest neighbor analysis (KNN) was used to classify participants with regard to likelihood of LTBI. Concentrations of MCP-2, IP-10 and IL-1ra were higher in QFT-borderline compared to QFT-low participants in both antigen stimulations (p < 0.001). KNN classification indicated high likelihood of LTBI in 13/31 (42%) women with QFT-borderline IFN-γ results. MCP-2, IP-10 and IL-1ra expressed in whole blood after TB antigen stimulation may be considered as alternative biomarkers for classification of LTBI status in pregnant women with borderline QFT IFN-γ results.